2007
DOI: 10.1103/physrevb.75.155322
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ferromagnetic switching in ZnO:(Co, Mn) powders

Abstract: We report here on the magnetic properties of ZnO:Mn-and ZnO:Co-doped nanoparticles. We have found that the ferromagnetism of ZnO:Mn can be switched on and off by consecutive low-temperature annealings in O 2 and N 2 , respectively, while the opposite phenomenology was observed for ZnO:Co. These results suggest that different defects ͑presumably n-type for ZnO:Co and p-type for ZnO:Mn͒ are required to induce a ferromagnetic coupling in each case. We will argue that ferromagnetism is likely to be restricted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
48
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 39 publications
10
48
1
Order By: Relevance
“…We believe that ferromagnetic samples have more O terminated surfaces that are not suitable for carbonate growth. This is in accordance with the fact that annealing in oxygen atmosphere switches on the ferromagnetism, while annealing in nitrogen switches it off [9]. These findings are also in accordance with our discussion about O 1s spectrum.…”
Section: Resultssupporting
confidence: 81%
“…We believe that ferromagnetic samples have more O terminated surfaces that are not suitable for carbonate growth. This is in accordance with the fact that annealing in oxygen atmosphere switches on the ferromagnetism, while annealing in nitrogen switches it off [9]. These findings are also in accordance with our discussion about O 1s spectrum.…”
Section: Resultssupporting
confidence: 81%
“…Reports in favor of Zn vacancy (V Zn ) [8,16], O vacancy (V O ) [17,18] or Zn interstitial (I Zn ) [19] mediated ferromagnetism can be found. It is also found that the defect species involved in inducing ferromagnetism in one ZnO based DMS system may not be effective in similar others [4,7,20]. The site occupied by the dopant atom [16], its size, electronic configuration and defect decoration [9], lattice strain [21], band gap [5] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Also, by successive annealings in O 2 atmosphere, the ferromagnetism of Co:ZnO nanoparticles could be correlated with the presence of defects. 5 Before any claims of intrinsic ferromagnetism can be made, an extremely careful structural analysis must be done to exclude the presence of secondary phases 6 or nanocrystals 7 that can account for the observed ferromagnetism. This issue becomes even more acute in DMSs with low concentrations of magnetic transition metals ͑typically ϳ5%͒.…”
Section: Introductionmentioning
confidence: 99%